How do you multiply e^(( 3 pi )/ 8 i) * e^( 3 pi/2 i ) e3π8ie3π2i in trigonometric form?

2 Answers

= e^(((31pi)/8)i)=e(31π8)i

Explanation:

e^(((3pi)/8)i) * e^ (3(pi/2)ie(3π8)ie3(π2)i
e^(((3pi)/8)i) * e^(((7pi)/2)i)e(3π8)ie(7π2)i

e^(((3pi)/8)i)* e^ (((28pi)/8)i)e(3π8)ie(28π8)i
e^ (((3pi + 28pi)/8)(i+i) = e^(((31pi)/8)i)e(3π+28π8)(i+i)=e(31π8)i

cos(pi/8)-isin(pi/8)cos(π8)isin(π8) or -(-1)^(7/8)(1)78

Explanation:

Are you sure its e^(3pi/2)e3π2 not e^((3pi)/2)e3π2 because it makes more sense when you write it in trig form.

Remember this beauty?
e^(ipi)=-1eiπ=1
That was Euler's identity. This is the generalized formula:
e^(ix)=cosx+isinxeix=cosx+isinx

Therefore, we can break down the two terms involved:

e^(i3/8pi)=cos((3pi)/8)+isin((3pi)/8)ei38π=cos(3π8)+isin(3π8)

e^(i7/2pi)=cos((7pi)/2)+isin((7pi)/2)=0+i*(-1)=-iei72π=cos(7π2)+isin(7π2)=0+i(1)=i

e^(i3/8pi)=(e^(i3/2pi))^(1/4)=(-i)^(1/4)ei38π=(ei32π)14=(i)14
e^(i3/8pi)*e^(i3/2pi)=(e^(i3/2pi))^(1/4)*e^(i7/2pi)=(e^(i3/2pi))^(5/4)=(-i)^(5/4)=-(-1)^(7/8)ei38πei32π=(ei32π)14ei72π=(ei32π)54=(i)54=(1)78

Or

e^(i3/8pi)*e^(i7/2pi) = sin((3pi)/8)-icos((3pi)/8)ei38πei72π=sin(3π8)icos(3π8)

=cos(pi/8)-isin(pi/8)=cos(π8)isin(π8)